MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS MENGGUNAKAN STRATEGI PEMBELAJARAN INDEKS CARD MATCH SISWA KELAS VIII SMPN 30 MERANGIN - Surib (Pendidikan Matematika | STKIP YM Bangko, 2020)
This research was motivated by the low understanding of mathematical concepts of students of class VIII SMPN 30 Merangin. This is because the learning strategy that is often used is teacher-centered learning, learning only relies on teacher activity rather than student activity. Therefore, action is taken using the Index Card Match strategy. The instruments used to collect data in this study were observation sheets for the implementation of learning, teacher and student activity sheets, and written tests in essay form. Based on the results of the analysis, it was found that there was an increase in each cycle, where in cycle 1 the student average score of 45.45 increased to 77.18 in cycle 2 with an increase of 59.09%, for student activity it also increased, namely 78, 09% in cycle 1 increased to 86.91% in cycle 2 there was an increase of 8.82%. Thus it can be concluded that using the Match Card Index learning strategy can improve the understanding of mathematical concepts of class VIII students of SMPN 30 Merangin.